6a-a+7-5=

Simple and best practice solution for 6a-a+7-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-a+7-5= equation:


Simplifying
6a + -1a + 7 + -5 = 0

Reorder the terms:
7 + -5 + 6a + -1a = 0

Combine like terms: 7 + -5 = 2
2 + 6a + -1a = 0

Combine like terms: 6a + -1a = 5a
2 + 5a = 0

Solving
2 + 5a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 5a = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 5a = 0 + -2
5a = 0 + -2

Combine like terms: 0 + -2 = -2
5a = -2

Divide each side by '5'.
a = -0.4

Simplifying
a = -0.4

See similar equations:

| 3q+2(5-q)= | | 2n-6=n+4 | | -28+8x=-8(3x-1)-4 | | (X+2)3=128 | | 4(5-5x)=60 | | 7x-3=6x-9 | | 16-32/4 | | .55*12+17= | | 7w-5=-6+2(w-7) | | 34-4b=18 | | 10-3v=49 | | 5-2d+4d-7+w= | | -2-3(1-x)=(-2x+7) | | 2m+(-3)=24 | | 5x-3+9x=4x-9 | | 2/3-1=20 | | 3n+19=28 | | -8h-64h=-2(7h+3)+2h | | -4x+7x-8=3(x-3)-5 | | 8m+28=24 | | 9+4.5= | | .15*12+35= | | 9(2m-3)-4(5+3m)=-3 | | 4d+6=8 | | 3-3k=5b | | A=-13+-2h | | -3+4r-3r=-5r+7r | | 30-23k=5b | | 6(x+6)+6=6x+2 | | X^2=4.5 | | 9x-9=8x+3 | | 2.75x+3y=.375 |

Equations solver categories